Phase Behaviour of 1-Ethyl-3-methylimidazolium Thiocyanate Ionic Liquid with Catalytic Deactivated Compounds and Water at Several Temperatures: Experiments and Theoretical Predictions - Anantharaj, Ramalingam; Banerjee, Tamal (International Journal of Chemical Engineering, 2011)
Density, surface tension and refractive index were determined for the binary mixture of catalytic deactivated compounds with 1-ethyl-3-methylimidazolium thiocyanate {[EMIM][SCN]} at temperature of (298.15 to 323.15) K. For all the compounds with ILs, the densities varied linearly in the entire mole fraction with increasing temperature. From the obtained data, the excess molar volume and deviation of surface tension and refractive index have been calculated. A strong interaction was found between similar (cation-thiophene or cation-pyrrole) compounds. The interaction of IL with dissimilar compounds such as indoline and quinoline and other multiple ring compounds was found to strongly depend on the composition of IL at any temperatures. For the mixtures, the surface tension decreases in the order of: thiophene > quinoline > pyridine > indoline > pyrrole > water. In general from the excess volume studies, the IL-sulphur/nitrogen mixture has stronger interaction as compared to IL-IL, thiophene-thiophene or pyrrole-pyrrole interaction. The deviation of surface tension was found to be inversely proportional to deviation of refractive index. The quantum chemical based COSMO-RS was used to predict the non-ideal liquid phase activity coefficient for all mixtures. It indicated an inverse relation between activity coefficient and excess molar volumes.